(untitled) (Global Journal of Management and Business Research, 2019)
This study aimed to assess the effect of corporate disclosures on market returns of commercial banks at Nairobi security exchange (NSE). Specific objectives were to assess the effect of environmental disclosures, social responsibility disclosures. The study adopted the institutional theory, market efficient theory and agency theory to support the literature review on corporate disclosures in looking at banks income statement, statement of financial position and additional notes to establish its profitability, liquidity over time frame annual reports. This study adopted descriptive research design. The study targeted 11 commercial banks. Secondary data was collected using data collection schedule. Data was analyzed using descriptive and inferential statistics, a multiple linear regression model was used to establish the relationship between variables. The study was of great importance to theory of development and literature for investors, shareholders, managers and law makers in making knowledgeable decisions and regulations considering the financing patterns and strategies of financial stability in Kenya, based on findings, recommendation and suggestions to further the study. The correlation analysis was used in this study and regression model to establish the effect between corporate disclosure and market returns of commercial banks.